Relevance of lipoproteins, membranes, and extracellular vesicles in understanding C-reactive protein biochemical structure and biological activities - Potempa, Lawrence A.; Qiu, Wei Qiao; Stefanski, Ashley; Rajab, Ibraheem M. (Frontiers in Cardiovascular Medicine, 2022)
Early purification protocols for C-reactive protein (CRP) often involved co-isolation of lipoproteins, primarily very low-density lipoproteins (VLDLs). The interaction with lipid particles was initially attributed to CRP’s calcium-dependent binding affinity for its primary ligand – phosphocholine – the predominant hydrophilic head group expressed on phospholipids of most lipoprotein particles. Later, CRP was shown to additionally express binding affinity for apolipoprotein B (Apo B), a predominant apolipoprotein of both VLDL and LDL particles. Apo B interaction with CRP was shown to be mediated by a cationic peptide sequence in Apo B. Optimal apo B binding required CRP to be surface immobilized or aggregated, treatments now known to structurally change CRP from its serum soluble pentamer isoform (i.e., pCRP) into its poorly soluble, modified, monomeric isoform (i.e., mCRP). Other cationic ligands have been described for CRP which affect complement activation, histone bioactivities, and interactions with membranes. mCRP, but not pCRP, binds cholesterol and activates signaling pathways that activate pro-inflammatory bioactivities long associated with CRP as a biomarker. Hence, a key step to express CRP’s biofunctions is its conversion into its mCRP isoform. Conversion occurs when 1.) pCRP binds to a membrane surface expressed ligand (often phosphocholine); 2.) biochemical forces associated with binding cause relaxation/partial dissociation of secondary and tertiary structures into a swollen membrane bound intermediate (described as mCRPm or pCRP*); 3.) further structural relaxation which leads to total, irreversible dissociation of the pentamer into mCRP and expression of a cholesterol/multi-ligand binding sequence that extends into the subunit core; 4.) reduction of the CRP subunit intrachain disulfide bond which enhances CRP’s binding accessibility for various ligands and activates acute phase proinflammatory responses. Taken together, the biofunctions of CRP involve both lipid and protein interactions and a conformational rearrangement of higher order structure that affects its role as a mediator of inflammatory responses.